HOME ENVIRONMENT ON ACQUISITION OF LITERACY SKILLS AMONG EARLY GRADES LEARNERS IN TANZANIA - Lyimo, Agness (Journal of Early Childhood Education (JECE), 2023)
Literacy skills are essential in children’s future learning and development. Studies indicate that literacy skills among early grade learners in Tanzania are below the required standards. This study explored the contribution of home factors that hinder acquisition of reading and writing skills among early grades learners in Tanzania. The study was informed by a qualitative methodology and case study design. The study involved a total of 92 participants, including 80 parents and 12 standard one and two teachers from four primary schools in two districts of Morogoro region. The study employed purposive sampling technique to select teachers and convenience sampling technique to obtain parents who were involved in interview and focus group discussion. Data was collected using semi-structured interview, focused group discussion and documentary review. The data were analysed thematically based on themes and sub-themes emerged in the study. The findings revealed that most factors that hinder early grade learners from acquiring reading and writing skills included (poor parents fall up, engaging children in many home activities, low parents’ education and parent’s income) It was suggested that there should be cooperation between parents and teachers to assist the children in developing their reading and writing skills. The study concludes that parents and teachers should work collaboratively to develop reading and writing in children. Lastly, it is recommended that parents should buy materials like books, and they make time to assist their children at home.